Pengaruh Thin Capitalization, Komite Audit Dan Tax Avoidance Terhadap Transfer Pricing - Mellani Devita Putri; Dirvi Surya Abbas; Budi Rohmansyah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The purpose of this study is to determine the Effect of Thin Capitalization, Audit Committee, and Tax Avoidance on Transfer Pricing in Automotive Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 Period.This research uses a quantitative approach. The population in this study was 15 automotive companies listed on the Indonesia Stock Exchange. The sampling technique used is Purposive Sampling. Based on the established criteria obtained 9 samples of automotive companies. The type of data used in this study is secondary data. The method used in this study is a regression analysis of panel data.The results of this study show that simultaneously Thin Capitalization, Audit Committee, and Tax Avoidance together affect Transfer Pricing. Partially Tax Avoidance has a positive effect on Transfer Pricing, while Thin Capitalization and Audit Committee have no effect on Transfer Pricing.